TANGHIM BETWEEN APPLIED AND SEMANTIC FUNCTION IN ARABIC AND YORUBA: COMPARATIVE STUDIES/ Ø§Ù„ØªÙ‘Ù†ØºÙŠÙ… Ø¨ÙŠÙ† Ø§Ù„ÙˆØ¸ÙŠÙØ© Ø§Ù„Ø£Ø¯Ø§Ø¦ÙŠÙ‘Ø© ÙˆØ§Ù„ÙˆØ¸ÙŠÙØ© Ø§Ù„Ø¯Ù‘Ù„Ø§Ù„ÙŠÙ‘Ø© ÙÙŠ Ù„ØºØªÙŠ Ø§Ù„Ø¹Ø±Ø¨ÙŠÙ‘Ø© ÙˆÙŠÙˆØ±Ø¨Ø§: Ø¯Ø±Ø§Ø³Ø© ØªÙ‚Ø§Ø¨Ù„ÙŠØ© - Mahmoud-Mukadam, Abdur-Rasheed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The purpose of this paper is to demonstrate the existence of the toning phenomenon in the Arabic language and to explain its performance and functions to reveal a secret of the Arabic Fusha language through the treatment of this tonal phenomenon through its purpose and meaning and its general function.The first section deals with the concept of toning. The second topic deals with the characteristics of toning. The third section deals with the functions of toning. The fourth section deals with tone, and reference. Discusses the phenomenon of toning in the Arab heritage, and the sixth and final topic: look at the phone toning in the language of Yorba, the conclusion, including the results of the search and margins.The methodology used in this research is the descriptive approach, which describes the language itself as an objective description, through scientific data or samples obtained using the necessary research tools. The motivation to adopt this descriptive approach is twofold: its relevance to the study of linguistic phenomena is a careful study that is both revealing and accurate. Collect facts and information and explain them to arrive at a scientific description of those facts and information.